PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN PENGELOLAAN DANA BOS TERHADAP MUTU PENDIDIKAN SDN SE-KECAMATAN MAJALENGKA - Iyus Susnardi (Universitas Majalengka, 2021)
This research is motivated by the phenomenon of the low quality of education in State Elementary Schools in Majalengka District, marked by the non-fulfillment of all applicable educational standards, aiming to determine the development of human resources; management of BOS funds and the quality of education in public elementary schools; and the influence of boss fund management and human resource development on the quality of education. The study used a quantitative approach with survey methods, data collection techniques using a questionnaire with a Likert scale distributed to 238 respondents. Processing and analyzing data using a parametric statistical approach, analyzed descriptively and verification. The results showed; Human resources and Boss Fund have been well managed and developed; Simultaneously the development of human resources and management of BOS funds have a significant effect on the quality of education with a magnitude of 74.70% and the remaining 25.30% influenced by other factors not examined. The conclusion, either partially or jointly, is that the development of human resources and the management of BOS funds affect the quality of education in Public Elementary Schools in Majalengka District